2007
DOI: 10.1590/s0074-02762007005000040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative recognition by human IgG antibodies of recombinant proteins representing three asexual erythrocytic stage vaccine candidates of Plasmodium vivax

Abstract: In previous immuno-epidemiological studies of the naturally acquired antibody responses to merozoite sur-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 17 publications
5
30
0
14
Order By: Relevance
“…Purified PvAMA-1 produced in E. coli and P. pastoris were examined by ELISA with sera collected from 208 individuals during patent P. vivax infection (25). The results showed that 72.7% and 62.5% of the sera recognized E. coli PvAMA-1 and P. pastoris PvAMA-1, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purified PvAMA-1 produced in E. coli and P. pastoris were examined by ELISA with sera collected from 208 individuals during patent P. vivax infection (25). The results showed that 72.7% and 62.5% of the sera recognized E. coli PvAMA-1 and P. pastoris PvAMA-1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we showed that recombinant proteins expressed in E. coli based on the P. vivax AMA-1 sequence were recognized by IgG antibodies of a large fraction of malaria-infected individuals (23)(24)(25)(26). We also described that these recombinant proteins can induce high antibody titers in mice following a homologous (protein-protein) or heterologous (protein-adenovirus) regimen of vaccination (27).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibitory antibodies specific for the 19-kD C-terminal of P. falciparum MSP-1 were not correlated with delayed appearance of infection but, actually, declined significantly in 2 months after treatment, which might have contributed to the risk of reinfection. 27,37 Herein, all individuals were infected at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-rPyM2-MAEBL antibodies titers were determined by enzyme-linked immunosorbent assay (ELISA) as previously described (32). Plates were coated with recombinant protein at 200 ng/well.…”
Section: Methodsmentioning
confidence: 99%